KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN SIKAP RELIGIUS SISWA DI MAN 1 ACEH TENGGARA - M Mualif Abdullah; Maharia Maharia; Nasrun Salim Siregar (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to determine the personality of adult teachers, to determine the solid and stable personality of teachers and to determine the noble character of Islamic religious education teachers in cultivating religious attitudes at MAN 1 Aceh Tenggara. This research uses a qualitative type of research using data collection techniques, namely interviews. , observation and analysis of documents. Data analysis uses data reduction, data presentation and conclusion drawing and verification. The results of the research show that teachers are figures who are role models or role models for students, the characteristics of elementary school level students generally have an imitative nature and students see how the adults around them act and socialize in everyday life. In the process of forming the religious character of students at MAN 1 Aceh Tenggara, the strong & stable personality of Islamic religious teachers plays a very important role. As an Islamic teacher, of course you also play a role in educating, teaching, guiding, training and providing student learning. In forming the religious character of MAN 1 Aceh Tenggara students. Islamic religious teachers teach basic Islamic teaching values ​​that students must understand and remember as well as Islamic religious learning material in class.